Discourse on ethnomedicinal plants in ancient Malay medical manuscript for gastrointestinal diseases - Wardah Mustafa Din; Ros Mahwati Ahmad Zakaria; Puteh Noraihan Rahman (Penerbit Universiti Kebangsaan Malaysia, 2021)
Since ancient times, people have been using plants not only for a source of food, but also for a source of medicine. In the Malay culture, many ethnomedicinal plants are being used for various medicinal properties. This knowledge is recorded in many ancient Malay manuscripts that acknowledge many different local names of plants and its traditional uses and practices. This study will be discussing one of the ancient Malay manuscript named “Hikayat Nurul-lisan Menjawab Masalah” whereby the original work was written in Jawi alphabets. Fortunately, Harun Mat Piah in his book, “Kitab Tib Ilmu Perubatan Melayu” had transliterated the work to Latin alphabets and organised it to a better structure which makes the content readily accessible and easily interpreted for Malay researchers. The purpose of this study is to analyse and tabulate ethnomedicinal plants documented in the transliterated manuscript which mentioned gastrointestinal benefits. To attain the research objectives, qualitative thematic analysis will be employed on the manuscript in order to classify different themes in the text systematically. Among illnesses frequently mentioned in the manuscript are gastrointestinal related, such as digestion, bloating, diarrhea and others. The study highlights that there are 36 number of plants mentioned in the manuscript which relates to gastrointestinal diseases. There are many different practice of use, whereby some are with detailed explanation, and others very general. Some plants are mentioned as being used for the well-being of the digestive system. This study is imperative for comprehensively structuring the traditional knowledge obtained in the manuscript for easy reference and access to other researchers locally and internationally. Besides to enrich our traditional knowledge on ethnomedicinal plants, this research will indirectly serve to preserve one of an important Malay cultural heritage.